Evaluation of shear bond strength between thermosens as relining material and different denture base materials - Ghazwan A Alkinani (College of Dentistry/ University of Baghdad, 2014)
Background: Denture relining is the process of resurfacing of the tissue side of the ill fitting denture, the bond strength at the relining-denture base interface is most important for denture durability.The aim of present study was to evaluate the shear bond strength between the thermosens as relining material and different denture base materials that bonded by thermo fusing liquid. As this corrective procedureis the common chair side procedure in the dental clinic. Material and method: Sixty samples were prepared and divided into three main groups according to the type of denture base materials.Group (A) referred to the heat cure acrylic samples which consisted of 20 samples. Group (B) referred to the high impact acrylic samples which consisted of 20 samples. Group (C) referred to the thermosens samples which consisted of 20 samples. All groups then subdivided into two groups; each one consists of 10 samples, according to the surface roughness: (A1, B1and C1 for groups with surface roughness and A2, B2 and C2for groups without surface roughness). Each sample consisted of two similar parts represent the denture base material each part of the sample was designed with dimensions of (70mm X 12mm X 5mmlength, width and depth respectively) having a stopper of depth 3mm. One part of the sample was placed on the other in a manner thatleaving a space between them of dimensions (12mm X 12mm X 3mm length, width and depth respectively) to sandwich the relining material. Results: The results showed that the thermosens samples had the highest value of shear bond strength followed by the high impact acrylic samples, then heat cure acrylic samples which had the lowest value of shear bond strength. The results of present study showed that rough samples had reducedshear bondstrength in comparison with the smooth samples of the same denture base material.